Race, Gender, Higher Education, and Socioeconomic Attainment: Evidence from Baby Boomers at Midlife. - Conwell, Jordan A; Quadlin, Natasha (Social Forces, 2022)
This article investigates White, Black, and Hispanic men's and women's access and midlife labor market returns to college quality. To do so, we use data from the National Longitudinal Survey of Youth-1979 Cohort (NLSY-79), merged with college quality information from the Barron's Admissions Competitiveness Index. Although prior research has investigated similar dynamics in access and returns to higher education, this work typically excludes Hispanics and does not assess enrollments at community colleges and other less competitive colleges where Black and Hispanic enrollments tend to cluster. We find that Black–White and Hispanic–White differences in college quality, to Whites' advantage, were fully explained or reversed once we accounted for differences in students' backgrounds. At midlife, Hispanic and especially Black men had lower rates of labor force participation than White men who attended colleges of the same quality. Including such differences (i.e. years of no or part-time work) in assessing the earnings returns to college quality demonstrated striking disadvantages facing college-educated Black men relative to White men, which were not fully accounted for by background characteristics. Employment and earnings returns to college quality were not as disparate by race for women. Relative to White women, we find earnings advantages for Hispanic women among those who attended community colleges. This article demonstrates the utility of taking an intersectional and life course approach to the study of higher education and the economic returns to schooling.